I should try but I don’t: unpacking the different motivational and behavioral pathways of quantitative and qualitative job insecurity - An Hoang Kim Vo; Loi Thi-Hong Duong; Chi Ha-Lien Nguyen; Quynh Thi-Thao Nguyen; Linh Thi-Phuong Nguyen; Dung Thanh Pham (International Journal of Public Sector Management, 2026)
Purpose Public organizations in Vietnam are undergoing unprecedented restructuring. However, research on the outcomes of job insecurity in such contexts remains inconsistent. Grounded in self-determination theory (SDT), this study examines how quantitative and qualitative job insecurity differentially influence engagement in learning activities and unethical pro-organizational behavior. It further investigates these effects through two distinct motivational mechanisms: work self-determined motivation and work non-self-determined motivation. Design/methodology/approach A two-wave survey was administered to 267 public officers undergoing organizational restructuring. Structural equation modeling was employed to test the hypothesized direct and mediated relationships. Findings While quantitative job insecurity shows no significant effects, qualitative job insecurity is negatively associated with both engagement in learning activities and unethical pro-organizational behavior. However, the mechanisms underlying these effects differ. Specifically, qualitative job insecurity reduces engagement in learning activities through work self-determined motivation, whereas it reduces unethical pro-organizational behavior by lowering work non-self-determined motivation. These findings reveal that different forms of job insecurity have distinct impacts and operate through separate motivational pathways, helping to clarify previously mixed empirical results. Originality/value This study is among the first to integrate self-determination theory to explain inconsistencies in prior research on job insecurity. Conducted in Vietnam's unique restructuring context, it provides timely insights for public management and contributes to a more nuanced understanding of job insecurity's behavioral consequences.